SCOOPED EYES CAN BE USED FOR SEED POTATO PRODUCTION - Venkatasalam, E. P.; Singh, Sarjeet (Potato Journal, 2013)
A replicated field experiment on the performance of scooped eyes under field conditions was carried out at Shimla in a randomized complete block design with Indian potato cultivars Kufri Jyoti, Kufri Giriraj and JH 214 with whole tuber as a control. The emergence of whole tuber was 95 percent while employing scooped eyes it was 60 percent under rainfed conditions. The scooped eyes produced significantly higher number of tubers per m2 in all the varieties; among the varieties, hybrid JH 214 produced higher number of tubers per m2 (139.6). The increase in number of tubers was 182.0, 166.0 and 207.1 percent in cvs. Kufri Jyoti, Kufri Giriraj and hybrid JH 214, respectively over the control. The number of tubers weighing more than 100 g was significantly higher per m2 when of whole tubers were used (8.2 to 18.1), whereas, the number of seed-size tubers (20-100 g) was higher in the produce of scooped eyes. The scooped eyes significantly reduced the number and yield of over-size tubers. Using of scooped eyes is expected to reduce the cost of cultivation by decreasing the quantity of seed materials by 2.5 to 3.5 times in different varieties. For whole tuber the seed rate was 45 q / ha with an average tuber weight of 60 g and a population of 75,000 plants, while with scooped eyes it was only 8 q / ha with an average weight 5 g of each scooped eye. This saved the seed cost in two ways i.e. i) weight-wise on initial cost of seed and ii) producing more number of seed tubers per stem, which is likely to cover more area for planting during subsequent seasons. The left over portion of each tuber (without eyes) can be utilized as food or for extraction of starch and preparation of potato flour / potato brawn from the residue after proper drying and grinding. The sale of starch and flour / brawn will compensate the labour cost involved in scooping the buds. So the aseptically scooped eyes can be used for production of higher number of total and seed-size tubers which would reduce the cost of cultivation by decreasing the cost of seed material by 2.5 to 3.5 times, besides generating employment opportunities.